Proceedings of the 40th ACM Technical Symposium on Computer Science Education 2009
DOI: 10.1145/1508865.1509018
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing CS1 with robots

Abstract: We have developed a CS1 curriculum that uses a robotics context to teach introductory programming [1]. Core to our approach is that each student has their own personal robot. Our robot and software have been specifically developed to support the needs of a CS1 curriculum. We frame traditional problems (robot control) in terms that are personal, relevant, and fun. Initial trial classes have shown that our approach is successful and adaptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 10 publications
(2 reference statements)
1
14
0
Order By: Relevance
“…The designers and developers of the IPRE robot had an initial goal to address a wider audience and to incorporate elements of creativity to motivate students who do not fit the traditional computer science mold [Balch et al 2008;Kumar et al 2008;Summet et al 2009]. In this research setting, that goal was not met.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The designers and developers of the IPRE robot had an initial goal to address a wider audience and to incorporate elements of creativity to motivate students who do not fit the traditional computer science mold [Balch et al 2008;Kumar et al 2008;Summet et al 2009]. In this research setting, that goal was not met.…”
Section: Resultsmentioning
confidence: 99%
“…The desire to strive for students to bring in creative concepts and storytelling through robots via openended assignments to increase motivation was also a consideration [Balch et al 2008]. Additionally, the design for the robot and its curriculum was also meant to expand preconceived notions of computing [Summet et al 2009]. However, no data are provided in these articles that investigates whether these goals have been achieved.…”
Section: Robots In the Classroommentioning
confidence: 99%
See 2 more Smart Citations
“…Students learned to program by controlling a small robot using Python [3]. Our evaluation of this effort suggested that robotics was not significantly more motivating or having a greater impact on retention than our traditional course [40]. One explanation for this finding is that students did see the relevance of the context of robotics, but it did not motivate them.…”
Section: Explaining the Retention Effectmentioning
confidence: 79%